Successful management of Leydig Cell Tumor in a 65-year-Old patient: A rare case report - Hasan Haydar; Ayham Qatza; Saja Karaja; Anagheem Alkhleef; Mohamad Yasin Lutfi; Habib Jarbouh (Urology Case Reports)
Leydig cell tumors (LCTs) are rare testicular neoplasms, representing 1–3% of all testicular tumors. A 65-year-old male presented with a painless left scrotal mass. Ultrasound revealed a 61 × 53 × 35 mm tumor with heterogeneous echogenicity and abundant blood supply. Radical orchidectomy was performed, and immunohistochemistry confirmed LCT with positivity for Inhibin A and calretinin, and negativity for CK, chromogranin, LCA, and low Ki67. Postoperative follow-up at 6 months showed improved condition, no scrotal masses, and normal tumor markers. Finally, LCTs in older males require differential diagnosis; hormonal activity impacts presentation. Conservative management and monitoring are crucial.